PEMANFAATAN PARIWISATA TERHADAP KEBERLANJUTAN LAHAN PERTANIAN DI BALI - Wicaksana, Gde Bagus Andhika; Putra, I Wayan Yogik Adnyana (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
The relationship between tourism sector to the agricultural sector in bali causes the number of land conversion and change the function of agricultural land on a large scale. The area of agricultural land in bali has decreased to an average of 1,000 ha per year, due to the conversion of agricultural land to non-agricultural land as an impact from development of the tourism sector. Land conversion in bali province affects subak's existence as a permanent institution form related to irrigation water management, socio-agrarian, religious and economic dimension activities. In these areas, the growth of villas and condotels is the major factor of increasing land prices that affect the conversion of agricultural land. the price of fringe area of a tourism area is about 1/2 -3/4 the price of land, the effect of increasing land prices actually decrease the amount of land. To reduce the impact of tourism in changing the function of land especially agricultural land, can be done with strategies such as increasing land value subak through the use of tourism in the form of agrotourism, increased land value subak land through the use of world cultural heritage by unesco and reduction of agricultural land conversion through land pricing and revenue through government support.